Toward a consensus on the mechanism of nuclear pore complex inheritance - Lusk, C Patrick (Landes Bioscience, 2014)
Nuclear compartmentalization is achieved through the enclosure of the genome by the nuclear envelope; the nuclear envelope is perforated by nuclear pore complexes (NPCs), which form portals that control molecular exchange between the nucleus and cytoplasm. The number of NPCs per nucleus establishes a limit to the flux of molecules across the nuclear envelope and might directly impact genome organization and gene expression in a cell type specific manner. Mechanisms that control NPC number remain ill defined. Our recent study implicates a cytoplasmic pool of the nucleoporin Nsp1 as a factor that controls NPC number during the asymmetric division of budding yeast; Nsp1 acts to ensure that daughters inherit NPCs. We place our data within an emerging model of NPC inheritance in yeast and consider potential analogous mechanisms in multicellular eukaryotes, including the functional conservation of a cytoplasmic pool of Nsp1.